The Influence of Tax Incentive Policies and Trust in the Government Due to the Impact of Covid-19 on the Compliance of Individual Taxpayers of UMKM at KPP Pratama Pangkalan Kerinci - Vivian Regita; Andrew Jonathan Jaya; Murtanto Murtanto; Aris Riantori Faisal (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of: (1) Incentive Policy on Compliance of Individual Taxpayers of MSMEs, (2) Trust of the Government on Compliance of Individual Taxpayers of MSMEs. The data analysis technique used in this study is the Classical Assumption Test, T Test, F Test, and Coefficient of Determination Test (R²). The results of this study indicate that the Tax Incentive Policy and Trust in the Government has a positive and significant effect on the Compliance of Individual Taxpayers of MSME Actors registered at KPP Pratama Pangkalan Kerinci.